2022
DOI: 10.1038/s41598-022-06081-2
|View full text |Cite
|
Sign up to set email alerts
|

Immediate voluntary activation deficits following submaximal eccentric contractions of knee extensors are associated with alterations of the sense of movement

Abstract: The mechanisms underlying movement sense alterations following repeated eccentric contractions remain unclear. This study concomitantly investigated the effects of unilateral eccentric contractions on movement sense and on neuromuscular function at the knee before, immediately after (POST), 24 (POST24) and 48 (POST48) h after the exercise. Twelve participants performed sets of submaximal knee extensors (KE) eccentric contractions until a 20% decrease in maximal voluntary isometric contraction (MVIC) torque was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…MVICs were performed at the end of each set. Exercise was stopped when 20% MVIC force decrement was reached to correspond to fatigue levels achieved in studies on knee extensors (Da Silva et al 2021Silva et al , 2022. An additional set of 6 eccentric contractions was performed between the seated and prone JPM tasks described below to maintain the target force loss during the POST condition (Fig.…”
Section: Unilateral Kf Eccentric Boutsmentioning
confidence: 99%
See 1 more Smart Citation
“…MVICs were performed at the end of each set. Exercise was stopped when 20% MVIC force decrement was reached to correspond to fatigue levels achieved in studies on knee extensors (Da Silva et al 2021Silva et al , 2022. An additional set of 6 eccentric contractions was performed between the seated and prone JPM tasks described below to maintain the target force loss during the POST condition (Fig.…”
Section: Unilateral Kf Eccentric Boutsmentioning
confidence: 99%
“…In this experiment, participants performed JPM tasks in seated and prone positions so that KF were either antagonistic or agonistic during the positioning movement. Based on recent papers showing associations between impaired VA and kinesthetic alterations (Da Silva et al 2021Silva et al , 2022, it was hypothesized that knee position sense alterations would only be observed in presence of VA decreases. It was also hypothesized that knee position sense alterations would be attenuated after ECC2.…”
Section: Introductionmentioning
confidence: 99%